Judge Not: In Defense of Minority-Culture Arbitration - E. Gary Spitko (Washington University Law Quarterly, 1999)
In his article, The New Legal Process: Games People Play and the Quest for Legitimate Judicial Decision-Making, Professor Ron Krotoszynski warns that such minority-culture arbitration will further undermine the legitimacy of the federal and state court systems. Professor Krotoszynski fears that a “mass exodus” strategy for avoiding cultural bias in the public courts will sufficiently reduce the opportunities for inter-cultural interaction, such that the potential for harms from misunderstanding and prejudice will be exacerbated for those cultural minority members who have no choice but to litigate in the public court systems. In Professor Krotoszynski’s view, this “will only further cripple the ability of the public courts to earn the trust and confidence of particular cultural subgroups within the community.” Thus, Professor Krotoszynski fears a vicious cycle. This essay defends the merits of minority-culture arbitration. Minorityculture arbitration not only has great utility as a needed safe harbor from majoritarian bias, it also holds great promise as an instrument of systemic change.
Keywords: Arbitration & award; Homophobia; Dispute resolution (Law); Gays; Mediation; Minorities